Learning difficulties: watching the context factors (2019)
This book seeks to contribute to address the challenges of education with the quality demanded by the 21st century world. It is based on the understanding and approach of learning difficulties, analyzed from the endogenous and exogenous factors of vulnerable contexts who demand a social and human pedagogy. The results presented are based on qualitative research, the hermeneutic approach and the ethnographic method. They showed the reality of the object of study, from the evidence and experience of their own actors: cycle 2 students, teachers, parents, teaching directors and support staff of the Educational Institution La Despensa, (Soacha, Colombia). The content of the book answers the question: what are the factors of the context that influence the learning difficulties of the students of the institution under study, and what didactic strategies can support its transformation? The findings can be easily transferred to other educational environments with similar characteristics, common to different areas of the country and the Latin American region. In addition, the findings highlight the normative and pedagogical gaps that exist in the topic of learning difficulties, mainly in the pedagogical management by teachers, who have a peremptory challenge, projected to be trained in the subject to strengthen their educational performance and vocation at the service of the integral formation of the minors. Thus, Learning Difficulties... brings the reader closer to current educational trends that, from a human approach, address the complexity of an insecure world, which demands a reflective and critical vision of vulnerable contexts. All this, in relation to learning difficulties and the social responsibility that school, teachers, parents, the State -through the municipal authorities -and the society, in general, have to fulfill in order to train the child in the necessary competences of being, knowing, doing and living together, based on a dialogical construction of their life project that positively impacts their environment.